A geometric accuracy analysis and tolerance robust design approach for a vertical machining center based on the reliability theory. (September 2020) - Wu, Haorong; Zheng, Hualin; Li, Xiaoxiao; Wang, Wenkuan; Xiang, Xiping; Meng, Xiaoping
Highlights: Machine tool geometric accuracy analysis is the premise of achieving tolerance robust design. Geometric accuracy model needs experimental verification. Non-key geometric errors lead to cumbersome tolerance design processes. Accuracy prediction model is a function of tolerance robust design. Tolerance robust design process needs to consider machine tool cost. Abstract: In the present work, an endeavor was proposed a geometric accuracy analysis and tolerance robust design approach for a vertical machining center based on reliability theory. Based on the establishment of accuracy prediction model and key geometric error traceability, combined the prediction accuracy and processing performance requirements of machine tool, the limit state equation of machining accuracy is obtained, and a calculation model of machining accuracy reliability is derived based on reliability theory. The first-order and second moment method is used to obtain an approximate solution of machining accuracy reliability. Taking key geometric errors as tolerance robust design variables, using relationships with manufacturing costs and accuracy reliability, a machine tool cost-geometric tolerance robust design model was established, which is used to realize the tolerance robust design of a vertical machining center. The results show that the method can achieve economical and rational distribution of geometric accuracy in a vertical machining center.